2012
DOI: 10.3167/hrrh.2012.380308
|View full text |Cite
|
Sign up to set email alerts
|

Picturing Politics: Female Political Leaders in France and Norway

Abstract: This article explores images of high-level female politicians in France and Norway from 1980 to 2010, examining the ways in which they present themselves to the media and their subsequent reception by journalists. Women in French politics experience diffi culties living up to a masculine heroic leadership ideal historically marked by drama, conquest, and seductiveness. In contrast, Norwegian female politicians have challenged the traditional leadership ethos of conspicuous modesty and low-key presentation. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
3

Year Published

2013
2013
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
0
2
0
3
Order By: Relevance
“…Culture also plays a role and is often closely intertwined with gender. In a comparative study of political leaders in France and Norway, Krogstad (this author) and Storvik (2007Storvik ( , 2010 found that political leadership ideals in France are orientated towards what Max Weber (1968) calls charismatic authority exhibited through what we call 'effortless superiority'. Norwegian politicians, however, gravitate first and foremost towards a rational-legal dimension, as well as a more subtle form of charisma we call 'low key charm'.…”
Section: Simulated Presence and Credibility In The Time Of Broadmentioning
confidence: 98%
“…Culture also plays a role and is often closely intertwined with gender. In a comparative study of political leaders in France and Norway, Krogstad (this author) and Storvik (2007Storvik ( , 2010 found that political leadership ideals in France are orientated towards what Max Weber (1968) calls charismatic authority exhibited through what we call 'effortless superiority'. Norwegian politicians, however, gravitate first and foremost towards a rational-legal dimension, as well as a more subtle form of charisma we call 'low key charm'.…”
Section: Simulated Presence and Credibility In The Time Of Broadmentioning
confidence: 98%
“…Savremena teorijska i empirijska istraživanja vizuelne političke komunikacije obuhvataju različite periode i kontekste političkog života lidera, kandidata, visokih zvaničnika i drugih aktera i institucija politike. Na primer, istraživače zanima kako se predsednici tokom jednog mandata predstavljaju u novinskim fotografijama ili na zvaničnim vebsajtovima (Lee 2016) ili kako se vizuelni narativi određenih svetskih lidera grade kroz istoriju (Krogstad and Storvik 2010). Vizuelna istraživanja politike mnogo su češća u kontekstu predizbornih kampanja u tradicionalnim i društvenim medijima.…”
Section: Vizuelno Predstavljanje Političara U Tradicionalnim I Onlajn...unclassified
“…Vizuelna istraživanja politike mnogo su češća u kontekstu predizbornih kampanja u tradicionalnim i društvenim medijima. Tako je zanimljivo videti na koji način se proučavaju Fejsbuk fotografije kandidata za opšte izbore u Sjedinjenim Američkim Državama (Goodnow 2013), ili šta govore Fejsbuk slike rumunskih kandidata za izbore za Evropski parlament (Cmeciu 2014), po čemu se u vizuelnoj predizbornoj komunikaciji razlikuju Nikola Sarkozi u Francuskoj i Angela Merkel u Nemačkoj i šta to znači za politiku uopšte (Flicker 2013;Krogstad and Storvik 2010), kako švedski političari koriste Instagram za vođenje kampanje (Ekman and Widholm 2017; Russmann and Svensson 2017), a kako austrijski kandidati za predsednika koriste vizuelni storiteling na Instagramu (Liebhart and Bernhardt 2017) itd. Istraživanja se nekad fokusiraju na pojedinačne događaje, kao što je analiza legendarne fotografije Baraka Obame u sobi za vanredne situacije (McFarlan 2016) ili na pojedinačne koncepte, poput vizuelne pismenosti (Edwards 2012;Messaris 1997) i "selebriti" politiku (Wheeler 2013).…”
Section: Vizuelno Predstavljanje Političara U Tradicionalnim I Onlajn...unclassified
“…Compared to ads in France, UK or the US, Scandinavian ads remarkably lack appeals to leadership capabilities or international experience. Another study suggests that while female French politicians seek to project effortless superiority, their Norwegian counterparts seek to demonstrate conspicuous modesty (Krogstad & Storvik, 2012).…”
Section: The Scandinavian Rhetoric Of Egalitarianism Authenticity and Pragmaticalitymentioning
confidence: 99%